2005
DOI: 10.1097/01.ico.0000151548.46231.27
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the Appearance of the Keratoconic Cornea In Vivo by Confocal Microscopy and In Vitro by Light Microscopy

Abstract: The current study confirms the application of CM for assessing morphologic alterations to the epithelium, Bowman's layer, and stroma in keratoconus. Many of the tissue changes observed with CM could be reconciled with observations made using LM. This work provides a framework against which tissue changes in keratoconus can be studied in a clinical context in vivo using CM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
91
4
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(115 citation statements)
references
References 20 publications
13
91
4
7
Order By: Relevance
“…2 In our study there was a reduction in basal epithelium density within the keratoconic corneas. Hollingsworth et al 19,20 also demonstrated this reduction and found similar difficulties in obtaining consistent imaging of the superficial epithelial layers. These authors also reported evidence of epithelial elongation, although this was not seen in our study this could be due to differences in experimental methodology.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…2 In our study there was a reduction in basal epithelium density within the keratoconic corneas. Hollingsworth et al 19,20 also demonstrated this reduction and found similar difficulties in obtaining consistent imaging of the superficial epithelial layers. These authors also reported evidence of epithelial elongation, although this was not seen in our study this could be due to differences in experimental methodology.…”
Section: Discussionmentioning
confidence: 93%
“…One important difference between the two studies previously commented on is the corneal location examined (central cornea 19,20 vs corneal apex). Keratocyte cell density may not be uniform across the keratoconic cornea and this may explain the higher anterior and posterior keratocyte densities reported in our study.…”
Section: 39mentioning
confidence: 83%
See 2 more Smart Citations
“…Recently, Bitirgen et al observed a significant difference in the keratocyte density between mild and moderate keratoconus (22). Studies showed that keratocyte cell loss could be associated with the release of cytokines in the pathological process of the disease that causes the apoptosis of keratocyte (23,24). However, mechanical injuries in the epithelium due to eye rubbing or wearing of contact lenses could also lead to the release of apoptotic cytokines (25,26).…”
Section: Discussionmentioning
confidence: 99%